Consumption of An Anthocyanin-Rich Antioxidant Juice Accelerates Recovery of Running Economy and Indirect Markers of Exercise-Induced Muscle Damage Following Downhill Running - Lima, Leonardo C. R. [UNESP]; Barreto, Renan V. [UNESP]; Bassan, Natalia M. [UNESP]; Greco, Camila C. [UNESP]; Denadai, Benedito S. [UNESP] (Mdpi, 2019)
This study examined the effects of anthocyanin-rich antioxidant juice (AJ) on the recovery of exercise-induced muscle damage (EIMD) and the running economy (RE) following downhill running (DHR). Thirty healthy young men were randomly divided into two blinded groups and consumed either AJ or placebo (PLA) for nine days (240 mL twice-a-day). On day 5, the participants from both groups ran downhill (-15%) for 30 min at 70% of their maximal oxygen uptake (VO(2)max) speeds. The changes in RE (oxygen uptake (VO2) and perceived effort (PE) during 5-min runs at 80%VO(2)max) and EIMD (isometric peak torque (IPT), muscle soreness (SOR) and serum creatine kinase activity (CK)) were compared over time and between the groups on the 4 days following DHR. VO2 and PE increased (p < 0.05) immediately following DHR for both groups and remained elevated for PLA until 48h post-DHR while fully recovering 24 h post-DHR for AJ. SOR was greater (p < 0.05) for PLA throughout the study. CK increased for both groups and was greater (p < 0.05) for PLA at 96 h post-DHR. IPT decreased for both groups but recovered faster for AJ (72 h) compared to PLA (no full recovery). AJ accelerated recovery of RE and EIMD and should be used in specific contexts, but not chronically.
Keywords: running economy; antioxidant supplementation; anthocyanins; exercise-induced muscle damage; recovery; muscle soreness